Pengaruh Kinerja Keuangan Terhadap Return Saham Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Sari, Yuniar Diana, Imronudin, S.E. M.Si. Ph.D (2017)
This study bertujuau to analyze Return on Assets(ROA),Return on Equity(ROE), Net Profit Margin(NPM)and Gross Profit Margin(GPM)Return on shares in companies listed on the Indonesian Stock Exchange (BEI) in 2013-2014. The population in this research is manufacturing companies listed on the Stock Exchange in 2013-2014. The samples used were 19 companies listed on the Indonesian Stock Exchange (BEI) by using purposive sampling method. Data analysis method used is multiple linear regression analysis. The results based on hypothesis testing partially (t test) indicates that the ROE, NPM has no effect on stock returns. While ROA, GPM variable effect on stock returns.